2018
DOI: 10.3390/polym10121389
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Molecularly Imprinted Polymer of Spermidine and the Exploration of Its Molecular Recognition Properties

Abstract: Spermidine is a functional ingredient that can extend the lifespan of many foods and indicate meat safety. However, its synthesis and enrichment is expensive and complex. To develop an effective separation material that can offer highly selective recognition of spermidine, we first applied non-covalent molecular imprinting technology using methacrylic acid as a functional monomer, azobisisobutyronitrile as an initiator, and ethylene glycol dimethacrylate as a cross-linker. The adsorption properties of the poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…This is because B3LYP was not properly described with regard to dispersion interaction, a factor that has a significant role in noncovalent interactions [ 70 ]. Other hybrid functions such as ωB97xD and M062X represent alternative methods that better describe dispersion interactions [ 71 , 72 , 73 , 74 ]. ωB97xD is a long-range corrected hybrid density functional with damped atom–atom dispersion corrections and is more reliable for the calculation of the dispersion than earlier density functionals [ 75 ].…”
Section: Quantum Mechanics Methods To Design Mipsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because B3LYP was not properly described with regard to dispersion interaction, a factor that has a significant role in noncovalent interactions [ 70 ]. Other hybrid functions such as ωB97xD and M062X represent alternative methods that better describe dispersion interactions [ 71 , 72 , 73 , 74 ]. ωB97xD is a long-range corrected hybrid density functional with damped atom–atom dispersion corrections and is more reliable for the calculation of the dispersion than earlier density functionals [ 75 ].…”
Section: Quantum Mechanics Methods To Design Mipsmentioning
confidence: 99%
“…They found that interaction sites play an important role in the recognition process. The DFT was used to design a MIP for dinoteforan (DNF), namely by testing distinct functional monomers in various solvents [ 73 ]. Recoveries using rational and nonrational design (without computational approach) for the MIP were compared.…”
Section: Quantum Mechanics Methods To Design Mipsmentioning
confidence: 99%
“…Based on our previous work [34], choose the theory calculated optimum molar ratio of template molecules spermidine to the functional monomer methacrylic acid 1:4 as the experimental polymerization ratio. Accurately weighed 217.5 mg spermidine and 100 mg azobisisobutyronitrile, accurately measured 510 mL of meth acrylic acid and 2 mL of ethylene glycol dimethacrylate, mixed in a beaker.…”
Section: Spermidine Molecularly Imprinted Polymer Film Preparationmentioning
confidence: 99%
“…Subsequent removal of the template results in the specific recognition cavities that act as molecular recognitions sites to achieve specific binding of the target molecule. With the advantages of specific recognition ability, good stability and uncomplicated synthesis process, MIPs have attracted considerable attention in many fields such as purification and separation [2,3,4,5,6,7,8,9], chemo-sensing [10,11] catalysis [12,13,14] and drug delivery. Currently, most MIPs are based on non-covalent mechanisms and were synthesized in non-polar or less polar solvents by the interaction of hydrogen bonding between the functional monomer and template molecule; they are normally only compatible with non-aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%